Infectious diseases of the Philippines - Berger, Stephen A.; EBSCOhost eBook Collection (Los Angeles, Calif. Gideon Informatics, 2011)
Infectious Diseases of the Philippines is one in a series of GIDEON ebooks which summarize the status of individual infectious diseases, in every country of the world. Data are based on the GIDEON web application (www.gideononline.com) which relies on standard text books, peer-review journals, Health Ministry reports and ProMED, supplemented by an ongoing search of the medical literature.Chapters are arranged alphabetically, by disease name. Each section is divided into four sections:1. Descriptive epidemiology 2. Summary of clinical features3. Status of the disease in the Philippines 4. References.
Electronic reproduction.
Keywords: Communicable diseases -- Philippines; Electronic books